The Cheticamp pluton: a Cambrian granodioritic intrusion in the western Cape Breton Highlands, Nova Scotia - Barr, Sandra M.; Macdonald, Alan S.; Blenkinsop, John (Canadian Journal of Earth Sciences, 1986)
The Cheticamp pluton consists of biotite granodiorite (locally megacrystic) in the north and museovite–biotite granodiorite in the south, in probable faulted contact. These two rock types, especially the biotite granodiorite, show a broad range in modal and chemical compositions. They are interpreted to be cogenetic, with the museovite–biotite grandiorite derived from the biotite granodiorite by crystal fractionation involving mafic minerals, plagioclase, and sphene. The overall peraluminous composition of the suite resulted from the fractionation process, probably enhanced by alteration, rather than from derivation from peraluminous source rocks.A seven-point, whole-rock, Rb–Sr isochron indicates an age of 525 ± 40 Ma. The pluton intruded dioritic rocks and quartzo-feldspathic gneisses, thus indicating Precambrian ages for these units. It probably also postdates the Western Highlands volcanic–sedimentary complex, a major undated stratigraphic unit in the Cape Breton Highlands. Although the age overlaps the range of Rb–Sr ages from plutons of the Avalon Terrane of the Appalachian orogen, the geological setting of the Cheticamp pluton differs from that of true Avalonian plutons, such as those in southeastern Cape Breton Island.